1965
DOI: 10.1037/h0022578
|View full text |Cite
|
Sign up to set email alerts
|

Conditions affecting acquisition of observing responses in the absence of differential reward.

Abstract: SUPPLEMENTAEY REPORTS 435 experiment. Differences demonstrated between the groups in these relationships are important in that an E using one or the other group could come to different conclusions from the results obtained from the same operation. The complex effect of the age variables in this study demonstrates the limitation of any general statement about the role of age in the reinforcing effect of sensory stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…Just such an increase in observing was shown by Roper and Zentall [12] as reward schedules thinned. While some studies have also manipulated the size of the reward [36][38], our model does not make any direct predictions about this. It is possible that adaptation would scale the response to the overall sizes of available rewards (as indeed found for phasic dopamine activity in [39]), and the metrics of this would have to be known in order to make predictions about disengagement.…”
Section: Resultsmentioning
confidence: 99%
“…Just such an increase in observing was shown by Roper and Zentall [12] as reward schedules thinned. While some studies have also manipulated the size of the reward [36][38], our model does not make any direct predictions about this. It is possible that adaptation would scale the response to the overall sizes of available rewards (as indeed found for phasic dopamine activity in [39]), and the metrics of this would have to be known in order to make predictions about disengagement.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore introduced a second task that equalized the opportunity for simple physical preparation (Mitchell et al, 1965) (“information delay task”, Figure 2A). Monkeys again chose between informative and random cues, but afterward a second cue appeared that was always informative on every trial.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, contemporary proponents of the Law of Effect (Rachlin and Herrnstein, 1969) would predict similar results for both positive and negative situations. A number of studies (Hendry, 1969;Mitchell, Perkins, and Perkins, 1965;Prokasy, 1956;Wyckoff, 1952) found that animals preferred signalled to unsignalled positive reinforcers. Hendry, for example, using pigeons and a concurrent chain procedure, found a decided preference for a multiple fixed-ratio fixed-ratio schedule to a mixed fixed-ratio fixed-ratio (mixed FR FR) schedule, with probability of reinforcement held constant.…”
Section: Discussionmentioning
confidence: 99%